Konsepsi Pendidikan Agama Islam dalam Menyikapi Modernitas - A Suradi (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
To face the flow of globalization, it is proper for Islamic education to assimilate Western modern science and technology. This is one way to pursue the backwardness of Muslims from western civilization. However, if the assimilation process is meticulously not performed it will have an impact on the attitude of following everything that comes from the West. This is what I call the process of materialistic westernization. Modernization and globalization can influence people's attitudes in both positive and negative forms. Among these are open-minded, more dynamic, unfettered old things that are conservative, and develop an anticipatory and selective attitude in judging things that will happen, or are happening.